2020
DOI: 10.1002/14651858.cd005573.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for induction of remission in ulcerative colitis

Abstract: Analysis 2.4. Comparison 2 Probiotics versus 5-aminosalicylic acid (5-ASA) (mesalazine), Outcome 4 Minor adverse events........ Analysis 2.5. Comparison 2 Probiotics versus 5-aminosalicylic acid (5-ASA) (mesalazine), Outcome 5 Serious adverse events...... Analysis 2.6. Comparison 2 Probiotics versus 5-aminosalicylic acid (5-ASA) (mesalazine), Outcome 6 Withdrawal due to adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 44 publications
2
73
0
4
Order By: Relevance
“…The methods and preparation of probiotic supplements in the included studies were different and it might have an influence on pooling the results. The response to probiotics intake might also have been influenced by a number of within-study factors, such as antibiotic use [ 46 ] and corticosteroid therapy [ 47 ]; moreover, the serum levels of hs-CRP is influenced by corticosteroid drugs [ 48 ]. Anyway, none of the seven included studies adjusted the mentioned confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The methods and preparation of probiotic supplements in the included studies were different and it might have an influence on pooling the results. The response to probiotics intake might also have been influenced by a number of within-study factors, such as antibiotic use [ 46 ] and corticosteroid therapy [ 47 ]; moreover, the serum levels of hs-CRP is influenced by corticosteroid drugs [ 48 ]. Anyway, none of the seven included studies adjusted the mentioned confounders.…”
Section: Discussionmentioning
confidence: 99%
“…This has generated interest in how probiotics may be harnessed to mediate the mucosal inflammation of IBD [ 22 ]. Different strains of probiotics have shown promise in the treatment of both active disease and the maintenance of disease remission in IBD [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In active IBD, there are additional efficacy differences found in UC and CD. Though there have been numerous studies investigating probiotic usage and outcomes in UC, the diversity of probiotic usage and variance in study design have limited the conclusions that can be drawn from meta-analyses [ 31 , 32 ]. This being said, there have been studies showing the therapeutic benefit of probiotics either alone or in conjunction with standard-of-care therapy in UC [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although probiotics have been recommended for adjunctive therapy for inducing and maintaining a remission of pouchitis and UC ( 57 , 58 ), the clinical efficacy of probiotics for inducing and maintaining a remission of UC is limited. Results from a recent review analyzing 14 randomized controlled trials including 865 participants show low-certainty evidence that probiotics induce clinical remission in active UC patients when compared with a placebo and little or no difference when compared with 5-ASA ( 71 ). Based on limited information, this review reported that the combination of probiotics and 5-ASA may slightly improve the induction of remission compared with 5-ASA alone in patients with mild, but not severe, disease ( 71 ).…”
Section: Intestinal Inflammatory Diseases and Cancermentioning
confidence: 99%
“…Results from a recent review analyzing 14 randomized controlled trials including 865 participants show low-certainty evidence that probiotics induce clinical remission in active UC patients when compared with a placebo and little or no difference when compared with 5-ASA ( 71 ). Based on limited information, this review reported that the combination of probiotics and 5-ASA may slightly improve the induction of remission compared with 5-ASA alone in patients with mild, but not severe, disease ( 71 ). In fact, the combination of probiotics with traditional IBD therapy is the most widely investigated treatment for UC patients in current clinical trials.…”
Section: Intestinal Inflammatory Diseases and Cancermentioning
confidence: 99%